Freedom of religion or belief: an international law commentary - Bielefeldt, Heiner (Oxford scholarly authorities on international law, 2016)
This commentary on freedom of religion or belief provides a comprehensive overview of the pressing issues of freedom of religion or belief from an international law perspective